The differential effects of bisphosphonates, SERMS (selective estrogen receptor modulators), and parathyroid hormone on bone remodeling in osteoporosis - Silvia Migliaccio (Dove Medical Press, 2007)
Silvia Migliaccio, Marina Brama, Giovanni SperaCattedra di Medicina Interna, Dipartimento di Fisiopatologia Medica, Università degli Studi di Roma “La Sapienza”, Italy Abstract: Osteoporosis is a skeletal metabolic disease characterized by a compromised bone fragility, leading to an increased risk of developing spontaneous and traumatic fractures. Osteoporosis is considered a multifactorial disease and fractures are the results of several different risk factors both extra- and intraskeletal. Thus bone fragility can be the end point of several different causes: a) failure to reach an optimal peak bone mass during growth; b) excessive bone resorption resulting in decreased bone mass and microarchitectural deterioration; c) inadequate formation upon an increased resorption during the process of bone remodeling. The pharmacological therapeutical options, available to date, are directed on prevention of fractures. The aim of this paper is to describe the activities and the mechanisms of action, as known at present, of the most used therapies for osteoporosis and their clinical implications. Improvement of knowledge in this field will allow us to further improve therapeutical choices and pharmacological interventions.Keywords: Osteoporosis, estrogens, bisphosphonates, SERMS, teriparatide, mechanism of action, fracture